Preparation process of room temperature rusting passivation anticorrosive coating containing phosphorus-nitrogen hyperbranched polyamide

CN122958933APending Publication Date: 2026-10-23GD POWER DEVELOPMENT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611037537.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

第一类环氧磷酸锌转锈涂料:基体为线性双酚A环氧树脂,分子链规整度高、分子间隙大,常温交联反应活化能48.6kJ/mol,环境温度低于15℃时交联速率下降62%,涂层内部永久孔隙率达12.7%,氯离子、水汽易沿孔隙渗透至钢铁基体;同时磷酸锌为无机小分子钝化剂,与环氧树脂相容性极差,储存3个月后出现明显分层沉降,无法实现长期稳定储存

Benefits of technology

(1)全温域常温适配,施工边界大幅拓宽:现有超支化聚酰胺涂料最低施工温度15℃,本发明可实现0℃低温带锈涂装,0-35℃全区间无需任何加热、保温设备,野外高寒地区无需配套施工热源,单平米施工能耗降低92.3%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958933A_ABST
    Figure CN122958933A_ABST
Patent Text Reader

Abstract

The application discloses a preparation process of a room-temperature rust-containing phosphorus-nitrogen super-branched polyamide passivation anticorrosive coating, a bifunctional phosphorus-nitrogen terminated super-branched polyamide matrix is prepared through three-step continuous room-temperature synthesis, and the matrix is matched with an aluminum dihydrogen phosphate-attapulgite nano composite passivation filler and a silane in-situ interface coupling process, so that 0-35 DEG C room-temperature non-heating coating, direct passivation and sealing of substrate surface residual floating rust are realized. The application is free of external heating in the whole process at 0-35 DEG C, and sand blasting and rust removal are not needed, so that St2-St3 grade rusted substrates can be directly coated, and three protections of iron rust chelation, pore plugging and anode passivation are simultaneously completed, the salt spray resistance of the coating breaks through 2900h, the VOC content is less than 12g / L, and the application meets the national mandatory standard GB 38507-2020 of low VOC anticorrosive coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of heavy-duty anti-corrosion organic polymer coating preparation technology, specifically to a process for preparing a room-temperature rust-passivating anti-corrosion coating containing phosphorus and nitrogen hyperbranched polyamide. Background Technology

[0002] The service life of existing steel structures in China generally exceeds 15 years. Wind turbine towers, cross-sea bridges, oil storage tanks, and other facilities commonly exhibit layered surface rust and porous secondary corrosion. Traditional anti-corrosion construction requires Sa2.5 grade sandblasting, costing 28-36 yuan per square meter, while also generating large amounts of hazardous rust dust. Sandblasting is also impossible in low-temperature, high-humidity outdoor environments. Existing commercial rust-removing coatings are mainly divided into two categories: epoxy zinc phosphate rust-removing coatings and tannic acid chelated rust-removing coatings, both of which have inherent technical limitations. The first type of epoxy zinc phosphate rust-converting coating has a linear bisphenol A epoxy resin as its matrix, which has high molecular chain regularity and large molecular gaps. The activation energy of the crosslinking reaction at room temperature is 48.6 kJ / mol. When the ambient temperature is below 15℃, the crosslinking rate decreases by 62%. The permanent porosity inside the coating reaches 12.7%, and chloride ions and water vapor can easily penetrate into the steel matrix through the pores. At the same time, zinc phosphate is an inorganic small molecule passivating agent with extremely poor compatibility with epoxy resin. After 3 months of storage, obvious stratification and sedimentation occur, making long-term stable storage impossible.

[0003] The second type of tannic acid chelated rust-inducing coating: relies on polyphenolic hydroxyl groups to complex rust Fe³ + It can only achieve surface rust chelation and cannot penetrate into the internal pores for corrosion. Moreover, the tannic acid chelate products have poor hydrolysis resistance, and the chelate layer decomposes and falls off after more than 720 hours of neutral salt spray testing. At the same time, the tannic acid system coating has insufficient resistance to ultraviolet aging, and the chalking level reaches level 2 after 18 months of outdoor service, which cannot meet the needs of long-term outdoor corrosion protection.

[0004] Hyperbranched polyamides have become the mainstream material for lightweight anticorrosive resins in recent years. Compared with linear polyamides, they have three major advantages: a three-dimensional spherical branched structure, high density of terminal functional groups, and low melt viscosity. Current methods for preparing hyperbranched polyamides all employ a high-temperature melt polymerization process with equimolar amounts of A2 and B3 monomers, at polymerization temperatures of 160-220℃. At these high temperatures, phosphorus is prone to oxidative dephosphorization, leading to the failure of the resin's passivation functional groups. Furthermore, current technologies have not achieved a directional distribution of phosphorus and nitrogen; nitrogen is concentrated in the molecular backbone while phosphorus remains free outside the system, making it impossible to simultaneously achieve both anodic passivation and rust chelation.

[0005] Further analysis of existing technologies reveals four major unresolved technical pain points: 1. Hyperbranched polyamides require high-temperature polymerization, and the insufficient thermal stability of phosphorus functional groups prevents the retention of passivation activity; 2. The interfacial energy difference between organic resins and inorganic phosphate-based passivation fillers is >12 mN / m, leading to interfacial delamination and blistering during long-term service; 3. Conventional one-step sand milling dispersion causes nanofiller agglomeration, blocking the active sites at the resin ends and reducing passivation efficiency; 4. Existing rust-resistant coatings can only transform the surface rust layer and cannot seal the capillary pores within the rust layer, resulting in continuous secondary corrosion. Based on these industry pain points, existing technologies cannot meet the requirements for outdoor, room-temperature, sandblast-free, and long-term weather-resistant rust-resistant corrosion protection, necessitating a novel room-temperature phosphorus-nitrogen hyperbranched polyamide coating preparation process. Summary of the Invention

[0006] To address the four major defects of existing high-temperature polymerized hyperbranched resins—degradation of phosphorus functional groups, delamination at the organic-inorganic filler interface, lack of rust layer pore sealing, and low-temperature curing failure—this invention provides a process for preparing a room-temperature rust-passivating anti-corrosion coating using phosphorus and nitrogen-containing hyperbranched polyamide. The entire process operates at 0-35℃ without external heating, eliminating the need for sandblasting, and enabling direct coating of St2-St3 grade rusted substrates. Simultaneously, it achieves triple protection through rust chelation, pore sealing, and anodic passivation. The coating exhibits salt spray resistance exceeding 2900 hours, with a VOC content <12g / L, meeting the national mandatory standard for low-VOC anti-corrosion coatings, GB 38507-2020.

[0007] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a process for preparing a room-temperature rust-passivating anti-corrosion coating of phosphorus and nitrogen-containing hyperbranched polyamide, comprising the following steps: S1. Synthesis of phosphorus and nitrogen bifunctional hyperbranched polyamide matrix at room temperature: In a sealed reactor at room temperature of 22-28℃, ethylenediamine and trimethylolphosphonopropionic acid were weighed at a molar ratio of 1:2.15. First, all the ethylenediamine and 40% of the total mass of propylene glycol methyl ether acetate were added to the reactor. The mixture was stirred at 320 r / min for 12 min to homogenize. Then, the remaining trimethylolphosphonopropionic acid and the remaining 60% of propylene glycol methyl ether acetate were added dropwise at a uniform rate over 95 min using a reverse dropwise method. After the dropwise addition was completed, the mixture was stirred at a constant temperature for 145 min. The trace amount of by-product water was removed under a vacuum of -0.075 MPa to obtain a phosphorus and nitrogen-containing hyperbranched polyamide stock solution with terminal amino groups and a number average molecular weight of 4200-4600 and a branching degree of 0.68-0.72. S2. Silane modification of nanocomposite passivated filler surface: Aluminum dihydrogen phosphate with a particle size of 25-45nm and attapulgite nanofibers with an aspect ratio of 18:1 are mixed at a mass ratio of 3.2:1 and added to an ethanol-deionized water volume ratio of 7:3 dispersion. The solid content of the filler is controlled at 22wt%. 1.4% of the total mass of the filler is added to γ-aminopropyltriethoxysilane. The mixture is hydrolyzed at 25℃ and 280r / min for 90min, centrifuged and filtered, and vacuum dried at 65℃ for 22min to obtain silane-modified composite passivated filler. S3, Two-phase stepwise dispersion formulation of coating: Step 1: Low-speed pre-dispersion: Add 8.2% polytetrafluoroethylene micro powder and 1.1% polyether modified silicone defoamer by mass of the polyamide stock solution obtained in S1, and disperse at 240 r / min for 18 min; Step 2: High-speed filler dispersion: Add S2 modified passivating filler (27.5% of resin stock solution by mass) and 0.9% ammonium polyacrylate dispersant, and high-speed mill at 1100 r / min until the slurry fineness is ≤22 μm; S4. Room temperature closed-loop curing: After sand milling, the slurry is sealed and cured for 24 hours at 25℃. The aggregated particles larger than 50μm are removed by filtration to obtain a finished anti-corrosion coating with rust passivation at room temperature. The ambient temperature of all processes is controlled at 0-35℃, with no external heating, ultraviolet irradiation, or high-temperature curing.

[0008] Furthermore, the molar ratio of ethylenediamine to trimethylphosphonopropionic acid in S1 fluctuates between 1:2.1 and 1:2.2, the reverse dropping time fluctuates between 85 and 105 min, and the vacuum degree for removing byproducts fluctuates between -0.07 and -0.08 MPa.

[0009] Furthermore, the pH of the ethanol-deionized water mixed dispersion in S2 was adjusted to 4.9-5.3 using glacial acetic acid, and dry nitrogen gas at a flow rate of 0.3 L / min was introduced during the silane hydrolysis modification process to isolate water vapor.

[0010] Furthermore, in the S3 low-speed pre-dispersion stage, the system viscosity is controlled at 4200-4800 mPa·s. In the high-speed sand milling stage, zirconia grinding beads are used with a bead-to-material mass ratio of 1.8:1 and the sand milling cycle is repeated twice.

[0011] Furthermore, the relative humidity of the S4 curing environment is controlled at 42%-55%, and the filter uses a nylon pleated filter element with a pore size of 45μm.

[0012] Furthermore, the components of the finished coating, by mass percentage, are: 59.2% phosphorus and nitrogen-containing hyperbranched polyamide stock solution, 27.5% silane-modified composite passivating filler, 8.2% polytetrafluoroethylene micro powder, 2.0% additives, and 3.1% propylene glycol methyl ether acetate.

[0013] Furthermore, the hyperbranched polyamide obtained by S1 synthesis has a phosphorus content of 2.35%-2.52%, a nitrogen content of 4.11%-4.36%, and a molar percentage of free phosphonic acid groups in the molecular side chain of 17.2%-18.5%.

[0014] Furthermore, after S2 modification, the silane grafting rate on the surface of the composite passivated filler is 5.4%-6.1%, and the water contact angle of the filler is increased from the original 32° to 71°-74°.

[0015] Furthermore, the coating application conditions are as follows: substrate surface rust grade St2-St3, surface rust thickness 20-120μm, ambient temperature 0-35℃, relative humidity ≤65%, and dry film coating thickness 85-110μm.

[0016] Compared with the prior art, the present invention has the following significant advantages: (1) Full temperature range adaptable to ambient temperature, greatly expanding the construction boundary: The lowest construction temperature of existing hyperbranched polyamide coatings is 15℃. This invention can achieve low temperature rust coating at 0℃, and no heating or insulation equipment is required in the entire range of 0-35℃. No supporting construction heat source is required in cold and high-altitude areas in the wild, and the energy consumption per square meter of construction is reduced by 92.3%.

[0017] (2) High retention of phosphorus passivation functional groups: The retention rate of phosphorus element in traditional high-temperature polymerization is 58.2%, while the retention rate of room-temperature polymerization in this invention is 94.7%. Under the same filler addition amount, the rust chelation efficiency is increased by 51.4%, and it can stably convert a 120μm thick layer of floating rust. The maximum rust layer thickness that can be treated by existing technology is only 60μm.

[0018] (3) Improved long-term corrosion and weather resistance: No red rust was observed after 2940h of neutral salt spray test (GB / T 10125-2021), which is 250% better than commercial epoxy rust-resistant coating (840h); the color difference ΔE=2.1 after 2000h of artificial ultraviolet aging is far lower than the national standard value ΔE≤5.0, and the outdoor service life is extended from 5 years to 12 years.

[0019] (4) Excellent storage and construction stability: The coating has no stratification or sedimentation after 12 months of sealed storage at room temperature, and the viscosity change rate is ≤7.2%; the adhesion to rusted substrates is 5.2MPa, which far exceeds the national standard requirement of ≥3.5MPa for rusted primers; the coating has no cracks when bent at 180°, and its flexibility meets the deformation adaptation requirements of steel structures.

[0020] (5) Environmental protection indicators meet the standards: No benzene or ketone highly toxic solvents are added, and the VOC content is 10.8g / L, which is far below the limit of 420g / L in GB38507-2020; it does not contain lead or chromium heavy metal anti-rust pigments, and the amount of construction dust emissions is reduced by 99.1%, eliminating the cost of treating hazardous waste from sandblasting. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 This is a schematic diagram of the microstructure of the phosphorus-nitrogen hyperbranched polyamide synthesized at room temperature according to the present invention. Figure 2 This is a schematic diagram of the microscopic protective structure of the cross-section of the rust-bearing substrate after coating with the coating of the present invention; Figure 3 This is a complete process timing diagram of the present invention. Detailed Implementation

[0023] The following will be combined with the appendix of the present invention. Figure 1-3 The technical solutions in the embodiments of the present invention are clearly and completely described herein. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0024] It should be noted that the terms "first" and "second" in this invention are used for descriptive purposes only and should not be construed as indicating or implying relative importance. The terms "connection," "installation," and "fixation," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.

[0025] This invention sets up 3 sets of embodiments and 2 sets of comparative examples. All embodiments strictly follow the parameters defined in the claims, with only minor adjustments within the parameter fluctuation range. The comparative examples respectively eliminate three innovative points. All tests are based on the current national coating testing standards, with an ambient temperature of 25°C and a humidity of 50%.

[0026] Example 1 S1 matrix synthesis: In a 50L enamel-lined reactor sealed at 25℃, 2.15 mol of ethylenediamine and 12.8 L of propylene glycol methyl ether acetate (40% of the total) were added, and homogenized at 320 r / min for 12 min. 4.62 mol of trimethylolphosphonopropionic acid and 19.2 L of propylene glycol methyl ether acetate (the remaining 60%) were added dropwise at a uniform rate for 95 min. After the addition was completed, the mixture was stirred at a constant temperature for 145 min. The water was removed under vacuum at -0.075 MPa for 28 min to obtain a phosphorus and nitrogen hyperbranched polyamide stock solution with a number average molecular weight of 4420 and a branching degree of 0.70. The phosphorus content was 2.43% and the nitrogen content was 4.22%.

[0027] S2 packing modification: 3.2 kg of aluminum dihydrogen phosphate and 1.0 kg of attapulgite were added to 42 L of ethanol / deionized water (7:3) dispersion, the pH was adjusted to 5.1 with glacial acetic acid, and 58.8 g of γ-aminopropyltriethoxysilane was added. Modification was carried out at 25℃ and 280 r / min for 90 min under nitrogen protection at 0.3 L / min. After centrifugation at 8000 r / min for 15 min, the packing was vacuum dried at 65℃ for 22 min. The silane grafting rate was 5.82%, and the water contact angle of the packing was 72.3°.

[0028] S3 stepwise dispersion: Take 59.2 kg of polyamide stock solution, add 4.85 kg of polytetrafluoroethylene micro powder and 0.65 kg of polyether modified silicone defoamer, disperse at a low speed of 240 r / min for 18 min; add 16.28 kg of modified filler and 0.53 kg of ammonium polyacrylate dispersant, and mill twice at 1100 r / min, with a zirconia bead ratio of 1.8:1, and the final slurry fineness is 21 μm.

[0029] S4 curing and filtration: Curing at 25℃ and 48% humidity in a sealed environment for 24 hours, followed by filtration with a 45μm nylon filter element to obtain the finished coating.

[0030] Construction Inspection: The substrate is Q235 steel plate with St3 grade rust, rust layer thickness of 92μm, dust removal only with a wire brush, and roller coating dry film thickness of 98μm. Inspection Results: Surface dry 2.1h, hard dry 17.3h; no red rust after 2940h of neutral salt spray; adhesion 5.2MPa; VOC 10.8g / L; UV aging 2000h ΔE=2.1.

[0031] Example 2 S1: Ambient temperature 22℃, monomer molar ratio 1:2.1, dropping time 85min, vacuum degree -0.07MPa; the resulting resin has a number-average molecular weight of 4210 and a branching degree of 0.68.

[0032] S2: Hydrolysis pH 4.9, silane addition 1.4%; filler grafting rate 5.41%, water contact angle 71.2°.

[0033] S3: Low-speed dispersion viscosity 4220 mPa·s, sand milling fineness 22 μm.

[0034] S4: Curing humidity 42%; finished coating salt spray test 2710h, adhesion 4.9MPa, other indicators meet the standards.

[0035] Example 3 S1: Ambient temperature 28℃, monomer molar ratio 1:2.2, dropping time 105min, vacuum degree -0.08MPa; the resulting resin has a number-average molecular weight of 4580 and a branching degree of 0.72.

[0036] S2: Hydrolysis pH 5.3, silane addition 1.4%; filler grafting rate 6.08%, water contact angle 73.9°.

[0037] S3: Low-speed dispersion viscosity 4780 mPa·s, sand milling fineness 20 μm.

[0038] S4: Curing humidity 55%; finished coating salt spray test 2880h, adhesion 5.1MPa, other indicators meet the standards.

[0039] Comparative Example 1 The monomer molar ratio was 1:2, the polymerization temperature was 180℃, the catalyst was 0.2% p-toluenesulfonic acid, and the remaining parameters were completely consistent with those in Example 1. Results: The phosphorus retention rate of the resin was 57.9%, the rust chelation failed, red rust appeared after 792 hours of salt spray testing, the coating was brittle, and it cracked after bending at 120°.

[0040] Comparative Example 2 Silane filler modification was cancelled, and all additives and fillers were simultaneously sand-milled at 1100 r / min in one step. Results: The nanofiller agglomerates had a particle size of 89 μm, delamination occurred at the organic-inorganic interface, blistering occurred at the coating edges after 6 months of application, and the adhesion dropped to 2.8 MPa.

[0041]

[0042] The Gibbs free energy of the conventional aliphatic polyamide amidation reaction is ΔG = -12.1 kJ / mol. The reaction is spontaneous at room temperature but extremely slow because the hydration layers of amino and carboxyl groups hinder molecular collisions. This invention uses trimethylolphosphonopropionic acid, where the empty d orbitals of the phosphorus atom can combine with water molecules to form hydration complexes, breaking the hydration layer on the monomer surface and increasing the probability of molecular collisions by 3.4 times. This allows for rapid amidation at room temperature without a catalyst. In the reverse feeding mode, an excess of amino groups is maintained in the system to avoid the carboxyl self-condensation side reaction. The excess free amino groups can subsequently form coordination bonds with ferrous oxide on the steel surface, improving substrate adhesion. GPC gel permeation chromatography analysis shows that the molecular weight distribution coefficient (PDI) of the reverse feeding product is 1.24, indicating a narrow distribution polymer, while the PDI of the forward feeding product is 1.79. The uneven molecular weight distribution leads to coating cracking, further validating the rationale for the reverse feeding method.

[0043] Tafel polarization curves were tested using an electrochemical workstation. The corrosion current density Icorr of the blank corroded steel plate was 9.24 × 10⁻⁶. -5 A / cm²; Icorr = 4.16 × 10⁻⁶ after coating in Example 1 -7 The corrosion current decreased by 99.55% (A / cm²). The mechanism can be divided into two pathways: the nitrogen pathway: the terminal amino groups of the resin adsorb onto the surface of the steel cathode, consuming electrons from the cathode oxygen reduction process and inhibiting oxygen evolution corrosion; the phosphorus pathway: the side-chain phosphonic acid groups ionize H+. + Lowering the local pH of the rust layer converts unstable γ-FeOOH into stable α-Fe2O3, while phosphonic acid oxygen atoms react with Fe. 3+ A five-membered chelate ring is formed, with a dissociation energy of 46.8 kJ / mol, far exceeding the water vapor destruction energy of 21.3 kJ / mol. It will not dissociate under normal water temperature conditions. The dual-element synergy achieves bidirectional electrochemical protection through cathodic corrosion inhibition and anodic passivation.

[0044] The surface of native attapulgite is enriched with silanol groups, with a surface energy of 62.4 mN / m, while the surface energy of hyperbranched polyamide is 29.0 mN / m. This large interfacial energy difference leads to spontaneous phase separation. The dual-terminal functional groups of γ-aminopropyltriethoxysilane respectively match the interfaces of the two phases: the siloxane end hydrolyzes and dehydrates and condenses with the silanol groups of attapulgite, eliminating hydrophilic sites on the inorganic surface; the amino end forms intermolecular hydrogen bonds with the carbonyl groups inside the polyamide molecule, constructing a flexible transition interface layer. The modulus of the transition interface layer is between that of the resin and the filler, which can offset the internal stress of the coating under wet-dry cycles and avoid interface cracking. A stepwise dispersion process first seals the hydrophilic hydroxyl groups of the resin to prevent the resin from absorbing water and thickening under high-speed shear, ensuring uniform dispersion of the filler.

[0045] The coating can be stored in a temperature range of -5℃ to 45℃ without stratification after 10 cycles of alternating high and low temperatures. This is because the hyperbranched spherical molecules encapsulate the nanofillers, inhibiting their gravitational settling, unlike linear resins which cannot withstand high and low temperature cycles. Application tolerance: The substrate surface can tolerate ≤8% surface oil contamination without degreasing pretreatment. The terminal amino groups of the resin can emulsify trace amounts of oil contamination without affecting coating adhesion. Application tools include roller coating, spraying, and brushing. Spraying requires no dilution, while roller coating only requires ≤3% solvent dilution. The application tolerance is significantly higher than conventional epoxy rust-resistant coatings.

[0046] All raw materials used in this invention are domestically produced industrial products: ethylenediamine and trimethylolphosphonopropionic acid have sufficient domestic production capacity; attapulgite is sourced from Xuyi, Jiangsu Province; and the silane additive has a 100% domestic production rate. The preparation equipment consists of a conventional enamel-lined reactor and a sand mill, eliminating the need for customized equipment. The cost of a single batch of 5000L for large-scale production is 13.2 yuan / kg, lower than the 16.8 yuan / kg cost of commercial epoxy rust-inducing coatings. A pilot-scale test has been completed on a wind turbine tower, demonstrating direct roller coating at a low outdoor temperature of 5℃. Six months of on-site inspection showed no blistering or rust recurrence, meeting the requirements for continuous industrial production.

[0047] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention. Technical features, process parameters, and formula fine-tuning not described in detail in the present invention are all contents that can be conventionally derived, substituted, and optimized by those skilled in the art based on the core technical solution of the present invention, and all fall within the scope of protection of the present invention.

Claims

1. A process for preparing a room-temperature rust-passivating and corrosion-resistant coating of phosphorus-nitrogen hyperbranched polyamide, characterized in that, Includes the following steps: S1. Synthesis of phosphorus and nitrogen bifunctional hyperbranched polyamide matrix at room temperature: In a sealed reactor at room temperature of 22-28℃, ethylenediamine and trimethylolphosphonopropionic acid were weighed at a molar ratio of 1:2.

15. First, all the ethylenediamine and 40% of the total mass of propylene glycol methyl ether acetate were added to the reactor. The mixture was stirred at 320 r / min for 12 min to homogenize. Then, the remaining trimethylolphosphonopropionic acid and the remaining 60% of propylene glycol methyl ether acetate were added dropwise at a uniform rate over 95 min using a reverse dropwise method. After the dropwise addition was completed, the mixture was stirred at a constant temperature for 145 min. The trace amount of by-product water was removed under a vacuum of -0.075 MPa to obtain a phosphorus and nitrogen-containing hyperbranched polyamide stock solution with terminal amino groups and a number average molecular weight of 4200-4600 and a branching degree of 0.68-0.

72. S2. Silane modification of nanocomposite passivated filler surface: Aluminum dihydrogen phosphate with a particle size of 25-45nm and attapulgite nanofibers with an aspect ratio of 18:1 are mixed at a mass ratio of 3.2:1 and added to an ethanol-deionized water volume ratio of 7:3 dispersion. The solid content of the filler is controlled at 22wt%. 1.4% of the total mass of the filler is added to γ-aminopropyltriethoxysilane. Hydrolysis modification is carried out at 25℃ and 280r / min for 90min. After centrifugation and filtration, vacuum drying at 65℃ for 22min yields silane-modified composite passivated filler. S3, Two-phase stepwise dispersion formulation of coating: Step 1: Low-speed pre-dispersion: Add 8.2% polytetrafluoroethylene micro powder and 1.1% polyether modified silicone defoamer by mass of the polyamide stock solution obtained in S1, and disperse at 240 r / min for 18 min; Step 2: High-speed filler dispersion: Add S2 modified passivating filler (27.5% of resin stock solution by mass) and 0.9% ammonium polyacrylate dispersant, and high-speed mill at 1100 r / min until the slurry fineness is ≤22 μm; S4. Room temperature closed-loop curing: After sand milling, the slurry is sealed and cured for 24 hours at 25℃. The aggregated particles larger than 50μm are removed by filtration to obtain a finished anti-corrosion coating with rust passivation at room temperature. The ambient temperature of all processes is controlled at 0-35℃, with no external heating, ultraviolet irradiation, or high-temperature curing.

2. The preparation process of a room-temperature rust-passivating and anti-corrosion coating of phosphorus-nitrogen hyperbranched polyamide according to claim 1, characterized in that, The molar ratio of ethylenediamine to trimethylphosphonopropionic acid in S1 fluctuates between 1:2.1 and 1:2.2, the reverse dropping time fluctuates between 85 and 105 min, and the vacuum degree for removing byproducts fluctuates between -0.07 and -0.08 MPa.

3. The preparation process of a room-temperature rust-passivating anti-corrosion coating of phosphorus-nitrogen hyperbranched polyamide according to claim 1, characterized in that, The pH of the ethanol-deionized water mixed dispersion in S2 was adjusted to 4.9-5.3 using glacial acetic acid. Dry nitrogen gas was introduced at a flow rate of 0.3 L / min during the silane hydrolysis modification process to isolate water vapor.

4. The preparation process of a room-temperature rust-passivating anti-corrosion coating of phosphorus-nitrogen hyperbranched polyamide according to claim 1, characterized in that, In the S3 low-speed pre-dispersion stage, the system viscosity is controlled at 4200-4800 mPa·s. In the high-speed sand milling stage, zirconia grinding beads are used with a bead-to-material mass ratio of 1.8:1 and the sand milling cycle is 2 times.

5. The preparation process of a room-temperature rust-passivating anti-corrosion coating of phosphorus-nitrogen hyperbranched polyamide according to claim 1, characterized in that, The relative humidity of the S4 curing environment is controlled at 42%-55%, and the filter uses a nylon pleated filter element with a pore size of 45μm.

6. The preparation process of a room-temperature rust-passivating anti-corrosion coating of phosphorus-nitrogen hyperbranched polyamide according to claim 1, characterized in that, The components of the finished coating, by mass percentage, are: 59.2% phosphorus and nitrogen-containing hyperbranched polyamide stock solution, 27.5% silane-modified composite passivating filler, 8.2% polytetrafluoroethylene micro powder, 2.0% additives, and 3.1% propylene glycol methyl ether acetate.

7. The preparation process of a room-temperature rust-passivating anti-corrosion coating of phosphorus-nitrogen hyperbranched polyamide according to claim 1, characterized in that, The hyperbranched polyamide obtained by S1 synthesis has a phosphorus content of 2.35%-2.52%, a nitrogen content of 4.11%-4.36%, and a molar percentage of free phosphonic acid groups in the molecular side chain of 17.2%-18.5%.

8. The preparation process of a room-temperature rust-passivating anti-corrosion coating of phosphorus-nitrogen hyperbranched polyamide according to claim 1, characterized in that, After S2 modification, the silane grafting rate on the surface of the composite passivated packing is 5.4%-6.1%, and the water contact angle of the packing is increased from the original 32° to 71°-74°.

9. The preparation process of a room-temperature rust-passivating anti-corrosion coating of phosphorus-nitrogen hyperbranched polyamide according to claim 1, characterized in that, Coating application conditions: Substrate surface rust grade St2-St3, surface rust thickness 20-120μm, ambient temperature 0-35℃, relative humidity ≤65%, dry film coating thickness 85-110μm.